A strategy for the reduction of formaldehyde concentration in a hospital pathology laboratory. Issue 1 (21st January 2019) - Ogawa, Masanori; Kabe, Isamu; Terauchi, Yasuhiro; Tanaka, Shigeru
Abstract: Objectives: Formaldehyde is routinely used in pathology laboratories. The threshold limit value of formaldehyde determined by American and Japanese organizations is 0.1 ppm, which is similar to the indoor air quality guideline value (0.08 ppm). Therefore, maintaining low formaldehyde concentrations in the workplace is imperative. The purpose of this study was to reduce the concentration of formaldehyde in a hospital pathology laboratory, in which approximately 15 000 pathological diagnoses are conducted yearly, using hardware and software interventions. Methods: Although this laboratory had various ventilation systems, the formaldehyde concentration was high. Based on the Japanese work environment measurement system, the workplace was categorized as control class III, suggesting that improvements to workplace conditions were required. First, engineering controls were implemented and workers were asked not to block the ventilation system and not to keep waste fluid tanks open. However, the workplace required further improvement. Next, using a video camera and a formaldehyde detector, we attempted to visually educate workers about how much formaldehyde is emitted from the sample container based on the type of action undertaken. Results: After the first intervention, the workplace improved to control class II. Control class II indicates that the workplace condition is between classes I and III; a good workplace condition is classified as class I. Although the work environment was still categorized as control class II after the second intervention, this intervention led to the further improvements. Conclusions: The hardware and software interventions and safe working habits were effective in improving the work environment.